The Relationship between Underweight and Primary Dysmenorrhea Occurrence in Senior High School Students in Surakarta - Gladys Octavia; Fitriyah .; Andri Iryawan (Nexus Kedokteran Komunitas, 2017)
Background : Primary dysmenorrhea is a common gynecological problem complained by female adolescents. It can affect their performance in carrying out daily activities. Underweight is known as one of primary dysmenorrhea risk factors. This research aims to determine the relationship between underweight and primary dysmenorrhea occurrence in high school students in Surakarta. Methods : This research used an observational analytical study by the cross sectional approach, with underweight as independent variable and primary dysmenorrhea occurrence as dependent variable. The subjects of this research were 11th grade female students of 7, 4, Warga, Batik 1 and Islam Diponegoro Senior High School in Surakarta. Data were collected through primary dysmenorrhea questionnaire and measurement of studentss height and weight. Research subjects that fulfilled the inclusion and exclusion criteria were 225, consisted of 200 subjects with normal weight and 25 subjects with underweight. The collected data were analyzed with Fishers Exact test. Result : The result of Fishers Exact test was 0.385 as p value. So, there was not significant relationship between underweight and primary dysmenorrhea occurrence of high school students in Surakarta. Conclusion : This study shows no significant relationship between underweight and primary dysmenorrhea occurrence in high school students in Surakarta. Keywords: underweight, dysmenorrhea, Body Mass Index